Soil Characterization and Classification for Agricultural Land Use Planning: A Study of Semi-arid Rajasthan - Ankit Kumar; Shyam Sunder Sharma; Chiranjeev Kumawat (Journal of the Indian Society of Soil Science, 2023)
Based on morphological, physical, physicochemical and chemical characteristics of soil, six representative soil profiles from the Phulera tehsil of Jaipur district of Rajasthan were studied for soil characterization and classification. Results revealed that the soils of the study area were dominantly dark yellowish-brown in colour, with loamy sand texture having a higher content of sand. These soils were poor in organic carbon content (0.8 to 3.5 g kg -1). The soils were moderately alkaline (pH 7.3 to 8.3) in reaction and non-saline (EC 0.02-1.21 dS m-1). The cation exchange capacity (CEC) in most of the profiles was low (3.99 to 8.32 cmol(p+)kg -1) and calcium (Ca2+) and magnesium (Mg2+) dominated the exchange sites on the colloidal complex. All the profiles were placed under Entisol due to the absence of a diagnostic sub-surface horizon. Due to the ustic soil moisture regime, hyperthermic temperature regime, and higher sand content, the soils were classified as sandy, mixed, hyperthermic Typic Ustipsamments. On the basis of major soil constraints and potentials, suitable land use plans has been suggested.